CATAMNESIS OF CHILDREN COVID-19 (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Purpose: to study the clinical course of a new coronavirus infection in the provision of specialized medical care to children in a hospital and post-mortem follow-up. Results: All patients had laboratory-confirmed infection with SARS-CoV-2 (the result of real-time PCR, specific for SARS-CoV-2, was positive). The patients were divided into severe patients, including 2 (4.6%) patients with severe cases on admission and 32 (74.4%) patients with moderate cases, hospitalization in the intensive care unit was not, the remaining cases 9 (21% ) the disease was mild. All sick children of COVID-19 were discharged with recovery. In the observed children of the course of COVID-19, an increase in body temperature was noted 88%, vomiting 58%, diarrhea 68%, cough 77%, shortness of breath 7%. Every fifth patient has pneumonia as the only symptom of the disease. In this case, in order to establish a diagnosis and timely prescribe therapy, it is necessary to conduct an X-ray examination of the chest cavity organs. In children, mild and moderate forms of the disease are predominantly found, and the possibility of radiological verification of pneumonia in a patient with good health is also revealed. Another striking characteristic of COVID-19 is that it affects several vital organs (for example, the lungs, the digestive tract and the nervous system), as evidenced by the clinical course of the disease.